Limits to regional integration - Dosenrode-Lynge, Soren Zibrandt von (The international political economy of new regionalisms series, 2015)
Examines eleven cases ranging from the lack of integration in the Arctic and the Middle East, to ongoing or progressing integration in Europe to uncover what 'blocks' regional integration, the results of which are used for developing new theoretical insights.